Beyond Consumption: Exploring Sensory, Symbolic, and Digital Influences in Gastronomic Tourist Behaviour (Evidence from Indonesia) - Marceilla Suryana; Eko Susanto; Dinarsiah Chendraningrum (E-Journal of Tourism, 2025)
This study develops and empirically tests an integrative model of gastronomic tourist behaviour by connecting symbolic, sensorial, digital, and emotional dimensions of travel experience. Data from Indonesian domestic tourists (n = 384) were collected through structured surveys and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). Results reveal that embodied gastronomic encounters—particularly haptic interaction with food and place—are the strongest predictors of emotional attachment, tourist loyalty, and destination advocacy. Place branding further amplifies this effect, while social media stimulation contributes meaningfully but only in support of direct sensory experience. In contrast, digital engagement and cultural immersion exert marginal influence, suggesting that virtual promotion or heritage framing alone cannot sustain culinary tourism. Theoretically, these findings sharpen debates on experiential consumption by demonstrating that bodily immediacy and affective resonance mediate the impact of symbolic or digital triggers on behavioural outcomes. This challenges cognitive and representational accounts that overstate narrative or mediated experiences in shaping loyalty. Practically, the study calls for gastronomic destinations to design strategies that privilege multisensory engagement—taste, texture, and atmosphere—while embedding them in emotionally charged storytelling. By foregrounding the primacy of embodied experience, this research reframes culinary tourism not as a matter of digital visibility or cultural rhetoric, but as a sensorially grounded pathway to durable advocacy in an experience-driven travel economy.